2001
DOI: 10.3136/fstr.7.191
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Plasticized-Zein Film as Affected by Plasticizer Treatments.

Abstract: Corn-zein is a protein polymer promising as a biodegradable food packaging film to overcome environmental pollution caused by the use of non-degradable petroleum-derived plastics. However, the brittleness of pure zein film requires that plasticizers be added. The effects of the proportion of polyethylene glycol (PEG) and lauric acid (LA) used as composite plasticizer on mechanical and barrier properties of zein-based film were observed. Flexibility of plasticized-zein films increased as the portion of PEG was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 8 publications
(9 reference statements)
2
21
0
1
Order By: Relevance
“…The zein-fatty acid layers were also related to the decreased rigidity and increased tensile strength of the plasticized zein films [46]. Similar decreases in water absorption of zein films derived from oleic, linoleic and lauric acid plasticization were also observed in other studies [36,45]. Wang et al performed in-depth investigations into zein-fatty acid interactions using surface plasmon resonance and atomic force microscopy techniques [30,55,56].…”
Section: Effect Of Plasticizermentioning
confidence: 60%
See 2 more Smart Citations
“…The zein-fatty acid layers were also related to the decreased rigidity and increased tensile strength of the plasticized zein films [46]. Similar decreases in water absorption of zein films derived from oleic, linoleic and lauric acid plasticization were also observed in other studies [36,45]. Wang et al performed in-depth investigations into zein-fatty acid interactions using surface plasmon resonance and atomic force microscopy techniques [30,55,56].…”
Section: Effect Of Plasticizermentioning
confidence: 60%
“…Other studies found that glucose could reduce the rigidity of zein films more significantly compared to galactose and fructose, while galactose could improve tensile properties and water vapor resistance of zein film more efficiently than fructose and glucose [53,54]. Generally, use of polar plasticizers resulted in the poor ability of film to provide a barrier to water vapor due to their inherent hydrophilic properties compared with amphiphilic plasticizers, although both types could improve the mechanical properties of the films [34,37,45]. The effects of plasticizers on oxygen permeability are more complicated, and controversial results were reported [45,52,57].…”
Section: Effect Of Plasticizermentioning
confidence: 98%
See 1 more Smart Citation
“…Essas interações com as moléculas de plastificante reduzem as forças intermoleculares facilitando o deslocamento relativo das cadeias [35] . Com o aumento da concentração de plastificante o espaço entre as cadeias aumenta, nestas condições a difusão é facilitada [36,37] , elevando a penetração de moléculas de água para o interior do filme. Com respeito ao ácido oleico (AO) como plastificante, Wang & Padua [38] registram que a permeação de água, principalmente na forma de vapor, é facilitada com um aumento do teor de plastificante em filmes de zeínas.…”
Section: A 1000 Sequência Complexa De Picos Devidos Principalmente Asunclassified
“…In order to overcome some of these drawbacks, many attempts have been made to use plasticizers to improve the flexibility of zein. Some plasticizers having high boiling point temperature were used to improve the flexibility of zein, include glycerol, [8] polyethylene glycol, [9,10] and fatty acid. [6] In these studies, however, the flexibility of zein material was improved at the price of a decrease of strength, and the problem of water resistance remained.…”
Section: Introductionmentioning
confidence: 99%